Using Second Life Platform for Improving English Language Skills: Students’ Perception - Hassan, Riad F.; Dzakiria, Hisham; Idrus, Rozhan M. (International Review of Management and Marketing, 2016)
Educational researchers have paid considerable attention to the use of virtual world platforms in order to support English learning process. The use of Virtual World has become increasingly popular compared to conventional methods. Second life is an example of a typical virtual phenomenon that has raised interest among educators around the world. Many educational institutions have turned to SL due to its immersive and interactive environment and offering classes to enhance their students’ proficiency skills. This study is intended to elicit Iraqi students’ perception of SL’s potential as a virtual platform to improve English language learning. A qualitative case study was conducted. Data was collected through interviews. The research findings show that the learners were in favour of SL’s potential in improving English language proficiency. SL is fun to use, and most important of all, the learners feel that it is a new alternative to English language learning and needs to be explored. Keywords: Second Life, English Learning, Students’ Perception, Social Constructivism JEL Classifications: I210, Z00